Salience and social security benefits - Christian N. Brinch; Erik Hernæs; Zhiyang Jia (University of Oslo, Department of Economics, 2015)
We study the effect of salience in the social security benefit system on labor earnings by exploiting kinks and notches in budget lines introduced by earnings testing and social security accrual mechanisms for 67-69 year old workers in Norway. An earnings test had large effects on labor earnings, while an accrual system discontinuity had no discernible effects. We interpret the difference as likely to be caused by a lack of salience in the accrual incentives: agents are not able or willing to take into account the value of future benefit increases when considering the relevant rewards to working.
Keywords: J14; H55; 330; labor supply; retirement earnings test; social security wealth; difference-in-differences